Preliminary development of a portal for lecturer web database system / Roslan Jamaluddin, Anis Hasliza Hashim and Annurizal Anuar - Jamaluddin, Roslan; Hashim, Anis Hasliza; Anuar, Annurizal (2005)
This paper discusses the development of a model for lecturer web database system. The database system is developed using the Microsoft Access 2000 as the database and Active Server Pages for the interface. The database has been developed using Relational Database Management System (RDBMS) model. The database comprises 4 major entities which are university, faculty, department and lecturer. There are 6 attributes for university, namely ID, university name, address, phone, fax, and website; 6 attributes for faculty, namely ill, faculty name, address, phone, fax, university; 6 attributes for department, namely ill, department name, address, phone, fax, and faculty; and 16 attributes for lecturer, namely, name, identity card no, department, phone no, email, academic qualifications, professional memberships, positions, teaching, research, publication, consultation, expertise, conference, service, and awards. The system is online and capable of running several functions such as data collection, search, report and user's information record. The system will be a part of e-learning application of which lecturers are able to put academic and teaching portfolio online. It will be the source of information for users to seek all sorts of expertise, research, seminars, consultancy and others.